Lansoprazole for recurrent abdominal pain in adolescents - Ade Saifan Surya; Selvi Nafianti; Melda Deliana; Supriatmo Supriatmo; Atan Baas Sinuhaji (Paediatrica Indonesiana, 2011)
Background Recurrent abdominal pain is common among adolescents. School absenteeism and lower quality of life are associated with severity of symptoms. Lansoprazole has been used to treat recurrent abdominal pain.Objective To investigate the effectiveness of lansoprazole as a treatment for recurrent abdominal pain in adolescents.Methods We conducted a randomized, double-blind, controlled trial from August 2009 to October 2009. Adolescents suffering recurrent abdominal pain were eligible for the study. Simple randomization was done to divide subjects into two groups. Groups received 30 mg of lansoprazole or placebo, once a day for 14 days. Before treatment, we performed laboratory and physical examinations. Pain frequency was measured in number of abdominal pain episodes per month. Duration was measured in minutes and pain intensity was measured by a pain rating scale. Drug efficacy was measured before, during and after intervention. Data was analyzed using Mann-Whitney U-test and t-test.Results One hundred sixteen recurrent abdominal pain patients were randomized into two groups of 58 patients. There were no statistically significant differences in pain frequency before and after treatment for either the lansoprazole group or the placebo group (P=0.083, 95%CI, -0.033 to 0.021 and P=0.096, 95%CI -0.376 to 0.031, respectively). In addition, there were no significant differences in frequency, duration, and degree of abdominal pain at baseline and after 1, 2 and 3 months of treatment between the two groups.Conclusion Lansoprazole was not more effective than the placebo for treatment of recurrent abdominal pain among adolescents.